Hypertonic dextrose spray as topical endoscopic hemostasis for non-variceal upper gastrointestinal bleeding - Hasan Maulahela; Amanda Pitarini Utari; Rabbinu Rangga Pribadi; Virly Nanda Muzelina; Saskia Aziza Nursyirwan (Society of Gastrointestinal Intervention, 2023)
Background : : Endoscopic hemostasis is the primary therapeutic method for gastrointestinal bleeding. Hemoclips and thermocoagulation are the most commonly used methods of endoscopic hemostasis to control non-variceal upper gastrointestinal bleeding (NVUGIB). Recent findings have proven that hypertonic saline has the ability to act as a topical hemostatic agent in gastrointestinal bleeding and has the advantages of being inexpensive and readily available. This study aimed to compare the efficacy of hypertonic dextrose solution spray as an endoscopic hemostasis method for NVUGIB to that of standard therapy (hemoclips and thermocoagulation). Methods : : This experimental prospective study included patients with NVUGIB in Cipto Mangunkusumo National Central General Hospital between February 2020 and December 2021. There were 32 patients each in the control and intervention groups. Patients in the control group were treated with epinephrine only or with hemoclips/thermocoagulation, while the intervention group received hypertonic dextrose solution (40%) spray with or without epinephrine as an endoscopic hemostatic method. Results : : In the 64 patients with NVUGIB, peptic ulcers were the most common cause of bleeding (39.2%). The Rockall scores varied greatly from 0-6, with the most frequent Rockall score being 2 (31.3%). Nearly half of patients (43.8%) had Forrest IB bleeding. Initial hemostasis was successful in 100% of the control group and 96.9% of the intervention group. There were no complications after endoscopic hemostasis in both groups. The occurrence of re-bleeding was the same in both groups (25.0%). Eleven patients (17.2%) died during the study period. No significant differences were found in the success rate of initial hemostasis and the re-bleeding rate of NVUGIB between the control and intervention groups. Conclusion : : This study showed that hypertonic dextrose solution (40%) spray had a hemostatic effect. Hence, we recommend hypertonic dextrose solution spray as an alternative to endoscopic hemostasis for NVUGIB.